Phloem development, growth markers, and sieve-tube longevity in two Neotropical trees - Angyalossy, Veronica; Pace, Marcelo R.; Marcati, Carmen R. [UNESP]; Evert, Ray F. (Brill, 2021)
This study provides a detailed analysis of phloem anatomy, development, the formation of cell types, differentiation, and sieve-tube element's longevity in two tropical arboreal species, Cedrela fissilis (Meliaceae, Rosid) and Citharexyhun myrianthum (Verbenaceae, Asterid), growing in natural populations in the semi-deciduous Atlantic Rainforest. We periodically collected samples from the main stem at breast height (1.3 m), during both the dry and the wet seasons. Differences in the cells produced at these different seasons suggest that annual growth increments in the phloem are present in both species, marked by files of terminal narrow sieve-tube elements radially grouped in Cedrela fissilis, and in assemblages of narrow sieve tubes and axial parenchyma in Cytharexylum myrianthum, both appearing at the end of the wet season. In Cedrela fissilis, where fiber bands are present, each fiber band marks the end of the early phloem, acting as an indirect annual growth ring marker. Sieve-tube element longevity varied for both species from 4-26 months, a result similar to that obtained in temperate species.
Keywords: Cambial seasonality; phloem growth rings; phloem anatomy; Verbenaceae; Meliaceae